1980
DOI: 10.1128/jvi.36.1.120-124.1980
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of mycoplasma virus type 2 with cellular components of Acholeplasma laidlawii strain JA1

Abstract: Mycoplasma virus type 2 was shown to adsorb specifically to intact cells, membranes, and lipoglycan of Acholeplasma laidlawii strain JA1 but not to these components of Acholeplasma oculi. The oligosaccharide chain of the lipoglycan defined the specificity of the receptor site since deacylation not only did not reduce adsorption but increased it threefold. Actual adsorption of virus to lipoglycan was demonstrated by sucrose density gradient separation of the virus-lipoglycan complex. A strain of A. laidlawii, J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The kinetics of attachment are usually described as a pseudofirst-order reaction (3,19,33). Such kinetics of adsorption of MV-L2 to A. laidlawii were described previously (1,17,26). Liss and Heiland studied the adsorption of MV-L2 to three different strains of A. laidlawii and found that viruses produced from one strain differed in their ability to adsorb to the other strains: adsorption was always faster to the homologous strain (17).…”
mentioning
confidence: 99%
“…The kinetics of attachment are usually described as a pseudofirst-order reaction (3,19,33). Such kinetics of adsorption of MV-L2 to A. laidlawii were described previously (1,17,26). Liss and Heiland studied the adsorption of MV-L2 to three different strains of A. laidlawii and found that viruses produced from one strain differed in their ability to adsorb to the other strains: adsorption was always faster to the homologous strain (17).…”
mentioning
confidence: 99%